High-resolution spectral domain optical coherence tomography features in adult onset foveomacular vitelliform dystrophy. Issue 9 (24th June 2010) - Puche, N; Querques, G; Benhamou, N; Tick, S; Mimoun, G; Martinelli, D; Soubrane, G; Souied, E H
Abstract : Purpose: To describe the different morphological features in adult onset foveomacular vittelliform dystrophy (AOFVD) using high-resolution spectral domain optical coherence tomography (OCT). Design: Prospective observational case series. Methods: Complete ophthalmologic examination, including spectral domain OCT, was performed in 49 consecutive AOFVD patients (60 eyes). Results: In 28/60 eyes, spectral domain OCT showed hyper-reflective clumps within the outer plexiform and outer nuclear layers. In 9/60 eyes, the photoreceptor inner segment/outer segment (IS/OS) interface appeared highly reflective like a shell all around the vitelliform material, and appeared irregular and discontinued in 27/60 eyes. The Verhoeff membrane was clearly visible at the border of the lesion, disappeared over the vitelliform lesion in 20/60 eyes, became thickened and less defined on the outer aspect of the lesion in 11/60 eyes, appeared without noticeable alterations in 10/60 eyes and not well defined in 19/60 eyes. The vitelliform material appeared as a highly reflective dome-shaped lesion (homogeneous in 14/60 eyes and heterogeneous in 36/60 eyes) located between the photoreceptor layer and the retinal pigment epithelium (RPE). In 10/60 eyes, the macular lesion appeared as hypo/a-reflective. The RPE appeared irregular in 14/60 eyes, with hyper-reflective mottling on its inner aspect. We observed discrete RPE detachments in 29/60 eyes. Conclusions: We hypothesise that early changes involve the layer between RPE and the IS/OS interface, first with vitelliform material accumulation beneath the sensory retina, and then with IS/OS alterations, pigments migration towards inner layers and fluid accumulation. These changes come with RPE alterations such as hypertrophy or sub-RPE deposits.